Publics in Global Politics: A Framing Paper - Janne Mende; Thomas Müller (Politics and Governance, 2023)
In IR and beyond, there is considerable debate about the ways global governance, the transnationalisation of publics, and changes in communication technologies have affected the interplay between publics and global politics. This debate is characterised by disagreements about how to conceptualise publics in the global realm—and whether or not they exist in the first place. We seek to contribute to this debate by disentangling the various meanings associated with publics in order to get a better grasp of how publics shape and are shaped by global politics. We do so in two steps. First, we distinguish four different manifestations of publics: audiences, spheres, institutions, and public interests. Second, we identify four key dynamics that affect the evolution and interplay of these manifestations in global politics: the distinction between public and private, changes in communications technologies, the politics of transparency, and the need to legitimise global governance. These interrelated dynamics reshape the publicness of global politics while sustaining the plurality of the publics that partake in it.